Does Digitalization Benefit Employees? A Systematic Meta-Analysis of the Digital Technology–Employee Nexus in the Workplace - Guangping Xu; Zikang Zheng; Jinshan Zhang; Tingshu Sun; Guannan Liu (Systems)
The adoption of digital technologies (DTs) in the workplace has emerged as a core driver of organizational effectiveness, and many studies have explored the intrinsic connection between the two. However, due to the wide range of subdivisions of employee performance, existing studies present inconsistent research conclusions on the implementation effects of DTs and lack a systematic review of their impact on employee psychology and behavior for large sample data. To address this issue, employing a random-effects model and a psychometric meta-analysis approach based on subgroup and meta-regression analyses, this study examines 106 empirical studies, comprising 119 effect sizes. The findings reveal that DTs exhibit a “double-edged sword” effect. On the bright side, DTs significantly enhance task performance, innovation performance, employee engagement, job satisfaction, and job efficacy. On the dark side, DTs aggravate service sabotage, withdrawal behavior, job burnout, and work anxiety and have a suppressive effect on job well-being, while their influence on turnover intention is non-significant. Furthermore, this study identifies the moderating effects of industry characteristics, technology usage types, and demographic factors on the relationships between DTs and behavioral and psychological outcomes. The research conclusions help clarify the logical relationship between DTs and employee psychology and behavior and provide explanations for the differentiated research conclusions of previous studies. This study provides information for scientific management decisions regarding DTs in the workplace.